Effect Of Addition Of Different Livestock Manure On Population Density Of Tubifex Sp. Using A Recirculation System - Aryzegovina, Reffi; Mayasari, Lisa; Roza, Sri Yenica (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Tubifex sp. is a natural food that fish larvae really like because it contains nutrients that are beneficial for fish growth. Tubifex sp. Generally found in shallow waters of low-flow rivers and to protect the source of Tubifex sp. As a natural food for fish larvae, cultivation must be done by adding nutrients to their food. The aim of this research was to determine the population density of Tubifex sp. by using various types of manure with a recirculation system. This research is an experimental study using a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment media used were chicken manure (P1), goat manure (P2), cow manure (P3), and chicken, goat and cow manure (P4). The calculation data was tabulated and analyzed using the SPSS program. Parametric data were analyzed using analysis of variance (ANOVA) with a confidence value of 95%. If there are differences between treatments, a BNT (Least Significant Difference) test will be carried out. Population density of Tubifex sp. for 30 days, the best was treatment P2 (77063 birds) by giving a mixture of 500 gr of goat manure with 500 grams of organic mud soil, followed by treatment P1 (19564 individuals) with a mixture of 500 grams of chicken manure and organic mud soil. 1500 gr, then followed by treatment P4 (15445 heads) with a mixture of chicken manure, goat manure, cow manure 166.6 gr 500 gr of cow and 1500 gr of organic mud.